Controls of the implementation of environmental protection measures during underground ore exploitation - Jovanović Ivan; Staletović Novica (Bakar)
Technological parameters also have an impact on the environment due to the exploitation of the ore deposit. Therefore, it is necessary to analyze and assess environmental risks in the approved exploitation area and take measures and conditions to prevent, reduce and eliminate harmful impacts on the environment and human health. The aim of the paper is to emphasize that it is important to manage the environment, that measures should be determined and taken to eliminate, prevent and reduce environmental impacts in order to meet the conditions for further uninterrupted operation of the mine without violating legal provisions regarding environmental protection.